Evaluation of Postoperative Analgesic Consumption After Emergency and Elective Cesarean Section - Tapar, Hakan; Karaman, Serkan; Dogru, Serkan; Karaman, Tugba; Dogru, Hatice Yilmaz (Gynecology Obstetrics & Reproductive Medicine, 2019)
OBJECTIVE: This study compares post-operative pain and analgesic consumption among patients who have undergone either an emergent or elective caesarean section. STUDY DESIGN: A total of 115 patients, comprised of 48 emergency caesarean section and 67 elective caesarean section patients, were enrolled in this prospective study. Pain intensity was evaluated with a numeric pain scale in the 1st, 2nd, 6th, 12th and 24th post-operative hours and total post-operative tramadol consumption within 24 hours was recorded for each patient. RESULTS: Total tramadol consumption for emergency caesarean section patients under general anesthesia was 222.91±56.52 mg and for elective caesarean section patients under general anesthesia was 181.71±55.38 mg (p<0.05). In patients under spinal anesthesia, total tramadol consumption was found to be 169.58±59.52 mg and 160.62±70.47 mg in emergency and elective cases respectively (p>0.05). CONCLUSION: Analgesic consumption for emergency caesarean section patients under general anesthesia was observed to be high.